2017
DOI: 10.1038/srep40401
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell Subsets Directing Neonatal Spleen Regeneration

Abstract: Development of lymphoid tissue is determined by interactions between stromal lymphoid tissue organiser (LTo) and hematopoietic lymphoid tissue inducer (LTi) cells. A failure for LTo to receive appropriate activating signals during embryogenesis through lymphotoxin engagement leads to a complete cessation of lymph node (LN) and Peyer’s patch development, identifying LTo as a key stromal population for lymphoid tissue organogenesis. However, little is known about the equivalent stromal cells that induce spleen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
(52 reference statements)
2
24
0
1
Order By: Relevance
“…Engraftment of stromal fractions isolated by enrichment based on cell surface markers led to the identification of a spleen organizer cell as an endothelial‐like CD31 + MAdCAM‐1 + cell . However, formation of ectopic tissue was also found to be dependent on the presence of mesenchymal PDGFRb + cells . Stromal cell lines derived from long‐term cultures of the spleen, which support in vitro hematopoiesis, have also been grafted under the kidney capsule and shown to accumulate HSCs and myeloid cells from the host .…”
Section: Harnessing Emh In the Spleen To Improve Hsc Transplantation mentioning
confidence: 99%
“…Engraftment of stromal fractions isolated by enrichment based on cell surface markers led to the identification of a spleen organizer cell as an endothelial‐like CD31 + MAdCAM‐1 + cell . However, formation of ectopic tissue was also found to be dependent on the presence of mesenchymal PDGFRb + cells . Stromal cell lines derived from long‐term cultures of the spleen, which support in vitro hematopoiesis, have also been grafted under the kidney capsule and shown to accumulate HSCs and myeloid cells from the host .…”
Section: Harnessing Emh In the Spleen To Improve Hsc Transplantation mentioning
confidence: 99%
“…For that, we used splenic stromal cells from neonatal rats, as these cells (and not lymphocytes) are fundamental for the regeneration of the spleen ( Tan and Watanabe, 2014 ). After, these authors ( Tan and Watanabe, 2017 ), identified that the stromal cell population MAdCAM-1 + CD31 + CD201 + is essential for the formation of new splenic tissues. Despite the complete regeneration of the splenic tissue, both studies used the renal capsule to transplant stromal cells individually, either due to the large local vascularization or due to the lack of ideal support for sowing the cells.…”
Section: Discussionmentioning
confidence: 99%
“…MAdCAM-1-positive stromal cells were found to play an important role in spleen tissue organogenesis. 29 MZ B cells, which are the most frequent cell type contacting MAdCM-1+ stromal cells, recirculate between the spleen and gut-associated tissues, and may depend on MAdCAM-1+ stromal cells for their survival and activity regulation . 28 It was also suggested that the specialized stromal marginal reticular cells form a barrier inside the MZ, which guarantees the maintenance of gradients necessary for positioning of migratory B and T cells in the WP.…”
Section: Discussionmentioning
confidence: 99%